1987
DOI: 10.1139/v87-169
|View full text |Cite
|
Sign up to set email alerts
|

Heat capacities and volumes in aqueous polymer and polymer–surfactant solutions

Abstract: . Can. J. Chem. 65, 990 (1987). The apparent molar volumes and heat capacities of aqueous mixtures of neutral polymers and ionic surfactants were measured at 25°C. The polymers chosen were poly(vinylpyrrolidone) (PVP) and poly(ethy1eneoxide) (PEO) and the surfactants were the C8, Clo, and C I 2 homologs of sodium alkylsulfates and the C l o , C12, and C16 homologs of alkyltrimethylammonium bromides. The polymer-surfactant interactions depend on the nature of both components and on the chain length of the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…The transfer volumes obtained for the 12-3-12 and 12-6-12 surfactants in polymer solutions bear remarkable similarity to those obtained for mixed dodecyltrimethylammonium bromide-alcohol systems (43)(44)(45). ing the characteristic surfactant-polymer interaction, such as the SDS/PEO or SDS/PVP system, where the variation of the polymer concentration brings about only marginal changes in the volume behavior as a function of surfactant concentration (46,47). The variations in the apparent molar volume of the gemini surfactants in aqueous Pluronic solutions is more indicative of a mixed micelle formation or solubilization process as observed for the short to medium carbon chain length alcohols and can be rationalized in a manner similar to that for the surfactant-alcohol systems by considering two concentration regions.…”
Section: Apparent Molar Volume Studiessupporting
confidence: 60%
“…The transfer volumes obtained for the 12-3-12 and 12-6-12 surfactants in polymer solutions bear remarkable similarity to those obtained for mixed dodecyltrimethylammonium bromide-alcohol systems (43)(44)(45). ing the characteristic surfactant-polymer interaction, such as the SDS/PEO or SDS/PVP system, where the variation of the polymer concentration brings about only marginal changes in the volume behavior as a function of surfactant concentration (46,47). The variations in the apparent molar volume of the gemini surfactants in aqueous Pluronic solutions is more indicative of a mixed micelle formation or solubilization process as observed for the short to medium carbon chain length alcohols and can be rationalized in a manner similar to that for the surfactant-alcohol systems by considering two concentration regions.…”
Section: Apparent Molar Volume Studiessupporting
confidence: 60%
“…They confirmed that the anionic surfactant, such as sodium dodecyl sulfate, which was associated with polymer, was indeed in the form of micelles that were attached to the hydrocarbon backbone of the polymer. This structure can also be verified by measurement of heat capacities and apparent molar volumes (8).…”
Section: Introductionmentioning
confidence: 65%
“…[8] will return to Huggins equation for pure polymer solution, and if ξ = 0, it will return to the viscosity equation for pure polyelectrolyte solution. The constant B and D can be estimated from the viscosity data of the surfactant-free polymer solution by Huggins viscosity equation.…”
Section: Influence Of Surfactant Concentration On the Relationship Bementioning
confidence: 99%
See 1 more Smart Citation
“…The electrostatic interactions between the polymer and surfactant groups are important [9,10]. It has been observed that the interaction between uncharged water-soluble polymer is much easier with more facile anionic surfactants [11][12][13]. The uncharged water-soluble polymers appear weakly associated [14,15] with cationic surfactants, and deriving forces responsible for cationic surfactant-water-soluble polymer interactions is poorly understood in comparison to that of anionic surfactants.…”
Section: Introductionmentioning
confidence: 99%